Effects of ellagic acid on extracted tooth socket healing in nicotinic diabetic rats / Mazen.M.Jamil Al-Obaidi - Al-Obaidi, Mazen.M.Jamil (Institute of Graduate Studies, UiTM, 2015)
The resorption of alveolar bone that occurs after tooth extraction leads to many esthetic and functional problems. Ellagic acid (EA) is a member of the flavonoid family that regulates various processes of bone function. Statins are speculated to increase bone formation. This study was designed to evaluate the healing of extracted tooth sockets in diabetic and non-diabetic rats administered with EA orally and treated with rousavastatin (RSV) locally in nicotinic and non-nicotinic rats. Sixty-four male Sprague– Dawley rats weighing 250-300 g were selected to conduct the tooth extraction experimental study. The rats were divided into two main groups. The first main group was considered as the non-diabetic group and divided into four sub-groups; (A) The tooth rat socket filled with RSV+ The rats treated with NaCl orally (RSV+NaCl). (B) The tooth rat socket filled with RSV + the rats treated with EA orally (RSV+EA). (C) The tooth rat socket filled with RSV + The rats injected with Ni (RSV+Ni). (D) The tooth rat socket filled with RSV + the rats injected with Ni + treated with EA (RSV+Ni+EA). The second main group was considered as the diabetic group and divided into four sub-groups: (A) The tooth rat socket filled with RSV+ the rats treated with NaCl orally (RSV+NaCl). (B) The tooth rat socket filled with RSV + the rats treated with EA orally (RSV+EA). (C) The tooth rat socket filled with RSV + The rats injected with Ni (RSV+Ni). (D) The tooth rat socket filled with RSV + the rats injected with Ni + treated with EA (RSV+Ni+EA)…